TSS: Traceability Software Solution, A Medical Equipment Sterilization Process Trace-Back System - Pipat Sookavatana; Bunyapon Usawalertkamol; Somchai Mongcolpitakkul; Tatchai Usawalertkamol; Amitta Pacharapha (My University, 2023)
In Thailand, there is a problem with the traceability system that still uses handwriting form. Paper and handwriting are becoming the weakness and errors in keeping a record of the sterilization process correctness. The proposed system is developed and compared with the other two existing systems in this paper. The comparison shows the functional difference in features for using the system in CSSD (Central Sterile Supply Department). In the comparison, the proposed system has more features to assist the process recording task. The result shows that the proposed system has more functions to assist the CSSD staff.
Keywords: Food Supply Chain Traceability; Advanced Manufacturing and Logistics Optimization; QR Code Applications and Technologies